Study of Quantum Field Based on the Hypothesis of the Absolute System of Reference: A Non-Relativistic Theory - Konstantinos Patrinos (New Trends in Physical Science Research Vol. 8, 2022)
The quantum field theory based on the assumptions of the absolute reference system is a classical nonrelativistic theory that is compatible with current quantum theory. When using the fundamental ideas of this hypothesis, one can draw this conclusion by comparing the theoretical outcomes of quantum electrodynamics. The wave equation, which takes the place of Schrodinger’s, is a traditional electromagnetic wave equation that was derived from the study of particle structure. The expression of the uncertainty principle results from the normal distributions of momentum and position or respectively energy and time. Because the relativistic relation of energy with momentum and mass also applies in the hypothesis of the absolute system of reference, using the classical wave equation, the Klein-Gordon equation is derived in the same form, with a slight differentiation due to the appearance of the Lorentz factor.